Digit preference in Iranian age data (Italian Journal of Public Health, 2012)
BACKGROUND: Data on age in developing countries are subject to errors, particularly in circumstanceswhere literacy levels are not high. A common error in age reporting is the tendency of rounding the agesto the nearest figure ending in ‘0’ or ‘5’ or to a lesser extent, to the nearest even number. Because of thistendency, commonly known as “digital preference”, age heaping occurs at certain ages.The aim of this study was to study this phenomenon and both Myers’ and Whipple’s Indexes wereemployed to identify the digit preference in Iranian national census, 2005.METHODS: Myers’ and Whipple’s Indexes were employed to study the pattern of digit preference. TheMyers' Blended Index shows heaping at ages ending in 0 and 5 years, and the pattern of heaping is pro-nounced for both urban and rural populations.RESULTS: The quality of age reporting for the 2005 census data was poor if compared to the 1995 censusdata. Digit preference occurred most often in the female population compared to male one, and in ruralareas compared to urban ones.CONCLUSIONS: It can be concluded that both males and females tend to misreport their ages before age60 especially in rural areas. So, whenever any data gathering regarding age information occurs, the IDcard should be used regardless of person's self report.
Keywords: Digit preference; Myers' Blended Index; Whipple’s Index; Age data